2021
DOI: 10.1002/pits.22506
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting and retaining school psychologists: The experiences of district level administrative supervisors

Abstract: A shortage of school psychologists has been evident since the profession was initially recognized as a distinct field, and there is insufficient research on what current administrative supervisors are doing to address this problem. This qualitative study examined the perceptions of district level administrative supervisors regarding recruitment and retention of school psychologists. Participants reported the following: (a) school psychology graduate programs do not producing enough school psychologists, (b) ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…No other studies have collected data on how district-level gifted education coordinators define their roles, how their positions are titled, or how they perform their roles. The roles and responsibilities of this national sample of district leaders had several common themes that align with leadership roles from education leadership literature: the gifted education coordinator as the instructional leader, as the program manager, and as the communication and collaboration liaison (DiScala et al, 2019;Honig, 2008;Stosich, 2020;Young et al, 2021). These roles are vital to student learning and achievement outcomes for gifted and academically advanced students.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…No other studies have collected data on how district-level gifted education coordinators define their roles, how their positions are titled, or how they perform their roles. The roles and responsibilities of this national sample of district leaders had several common themes that align with leadership roles from education leadership literature: the gifted education coordinator as the instructional leader, as the program manager, and as the communication and collaboration liaison (DiScala et al, 2019;Honig, 2008;Stosich, 2020;Young et al, 2021). These roles are vital to student learning and achievement outcomes for gifted and academically advanced students.…”
Section: Discussionmentioning
confidence: 87%
“…For example, in the state of Maryland alone, out of 24 school districts, 24 different job titles are used to refer to the person who oversees K-12 Research on the responsibilities of other district-level instructional leaders revealed some common responsibilities. These include but are not limited to the following: content expert, advocate, program monitor and evaluator, professional development facilitator, budget manager, and teacher evaluator (Dawson, 1972;DiScala et al, 2019;Honig, 2008;Stosich, 2020;Young et al, 2021).…”
Section: District Administrator Roles and Responsibilitiesmentioning
confidence: 99%